2016
DOI: 10.1590/s1518-8787.2016050005667
|View full text |Cite
|
Sign up to set email alerts
|

High risk of respiratory diseases in children in the fire period in Western Amazon

Abstract: OBJECTIVE To analyze the toxicological risk of exposure to ozone (O3) and fine particulate matter (PM2.5) among schoolchildren..METHODS Toxicological risk assessment was used to evaluate the risk of exposure to O3 and PM2.5 from biomass burning among schoolchildren aged six to 14 years, residents of Rio Branco, Acre, Southern Amazon, Brazil. We used Monte Carlo simulation to estimate the potential intake dose of both pollutants.RESULTS During the slash-and-burn periods, O3 and PM2.5 concentrations reached 119.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
(21 reference statements)
0
9
0
2
Order By: Relevance
“…In addition to environmental damage, forest fires expose the populations of affected areas to a large amount of pollutants, characterized by plumes of smoke from the burning of plant biomass (Barlow et al, 2019). In this sense, burning would become a public health problem, as evidenced in the study developed by Silva et al (2016), analyzed in this work.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition to environmental damage, forest fires expose the populations of affected areas to a large amount of pollutants, characterized by plumes of smoke from the burning of plant biomass (Barlow et al, 2019). In this sense, burning would become a public health problem, as evidenced in the study developed by Silva et al (2016), analyzed in this work.…”
Section: Discussionmentioning
confidence: 88%
“…The study conducted by Silva et al (2016) presented the results of a research conducted in the health area on the exposure of children to pollutants present in the air from biomass burning, in the city of Rio Branco-AC, part of the "deforestation arc". The burning of volatile organic compounds (VOC) present in forest biomass generates Ozone (O3) and this has a high degree of toxicity causing respiratory problems to the exposed population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Cuiabá, with fine particulate data estimated by CCATT-BRAMS, the risk of children hospitalization for respiratory diseases was up to 22% in the dry season, 4 coinciding with our values regarding lag days. A study also conducted in the Amazon Region identified toxicological risks from exposure to ozone, but not to fine particulate, whose concentrations reached 50 µg/m 3 12 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified an association between exposure to fine particulate and hospitalizations for respiratory diseases 8 9 , 10 , 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%